Inhaled iloprost induces long‐term beneficial hemodynamic changes in patients with pulmonary arterial hypertension receiving combination therapy - Kenichiro Yasuda; Shiro Adachi; Itsumure Nishiyama; Masahiro Yoshida; Yoshihisa Nakano; Toyoaki Murohara (Pulmonary Circulation, 2022)
Abstract Inhaled iloprost is an established treatment for pulmonary arterial hypertension (PAH). However, the long‐term hemodynamic changes that inhaled iloprost induces are unclear. Here, we retrospectively enrolled 18 patients with PAH who received inhaled iloprost as add‐on to oral combination therapy from December 2016 to January 2021 at our institute in Japan. We then examined the changes in hemodynamic parameters induced by iloprost in these patients during right heart catheterization (RHC). To examine the long‐term effects of iloprost, we repeated the RHC examination at follow‐up (median time to follow‐up, 8.5 months). During both catheterization procedures, iloprost was administered by using an I‐neb AAD system (Philips NV). In a comparison of pre‐inhalation values at the first and follow‐up RHCs, inhaled iloprost significantly improved mean pulmonary artery pressure (mPAP; 39.9 ± 7.8 to 32.5 ± 7.2 mmHg, p = 0.016) and pulmonary vascular resistance (PVR; 588.5 ± 191.7 to 464.4 ± 188.5 dyn s cm−5, p = 0.047). During the follow‐up RHC, in a comparison of the pre‐inhalation and best recorded values out to 30 min after the end of iloprost inhalation, iloprost significantly decreased mPAP (32.5 ± 7.2 to 30.0 ± 6.6 mmHg, p = 0.007) and PVR (457.8 ± 181.4 to 386.2 ± 142.8 dyn s cm−5, p = 0.025) and significantly increased cardiac output (4.19 ± 0.91 to 4.64 ± 1.01 L/min, p = 0.035). Iloprost may have not only acute vasodilation effects but also long‐term hemodynamic benefits in PAH patients receiving combination therapy.